Enteroscopia: Un desafío hecho realidad - Maiza Rodríguez , Eduardo (Revista Hospital Clínico Universidad de Chile, 1997)
ENTEROSCOPY The definition, development, types, indications, way of access, technical procedures and complications of the small bowell endoscopy is reviewed by the author. The results are listed in 29 patients, confirming the utility of the procedure according other authors.